What influences the dissemination of online rumour messages in social media: the role of message, communicator, channel and rumour features - Li, Boying (2019)
Social media enables efficient and easy exchange of information. However, this not only enhances the sharing of valid information but also facilitates the dissemination of rumours which may have harmful impacts on individuals, companies and the society. To manage the impacts of rumours, it is important to understand the drivers and patterns of online rumour message dissemination. Considering the uniqueness of social media as information exchange platforms, this thesis aims to understand the themes and traits of online rumour topics and messages. Moreover, traditional rumour theories often study individual motivation of rumouring; however, in social media, messages are mostly broadcasted and can be accessed by the public, diminishing the influences of individual recipients’ attributes. This thesis thus seeks to develop a message-level framework to delineate how message features, communicator features and channel features influence the dissemination of online rumour messages and how rumour features moderate those effects. Specifically, this thesis considers online rumour messages as persuasive messages. Combining rumour theories, persuasion theories, emotion theories and congruence theories, this thesis aims to investigate the roles of cognitive appeals (i.e. content unambiguity and source unambiguity), affective appeals (i.e. message pleasantness, activation and imagery), communicator attributes (i.e. communicator trustworthiness, proximity, social influence and likeability), communication channels (i.e. hashtag and @) and rumour features (i.e. rumour target reputation and rumour valence) in influencing online rumour message dissemination in social media. Furthermore, the patterns of online rumour message dissemination may vary across rumour topics. To deepen the understanding of rumour message dissemination, this thesis also aims to summarise topic-level dissemination patterns of online rumour messages. Based on the research aims and objectives, this thesis takes a multi-method research design. First, an exploratory qualitative content analysis was carried out to understand the types of online rumour topics and the themes of online rumour messages. The findings were used to support the development of research framework. Second, the research framework and corresponding hypotheses were tested quantitatively using regression. Third, linguistic analyses were applied to describe how rumour messages vary across different types of rumour topics, and the effects of research framework were compared. Qualitative exploration finds that an online rumour topic may target a business’s brand, its offerings, its people or its operations and may focus on what happens, why or with what impacts. Results of regression analysis reveal that expression certainty, emotional activation, community communication and communicator attributes are positively associated with the number of retransmissions (i.e. the number of retweets in this research context) of online rumour messages, whereas the source explicitness, source accessibility, emotional pleasantness, emotional imagery and direct communication are negatively associated with the number of retransmissions. In addition, both topic-congruence (i.e. congruence between rumour target reputation and rumour topic valence) and message-congruence (i.e. congruence between rumour target reputation and rumour message valence) play important moderating roles. Results also show that for different types of rumour topics, the effects of cognitive and affective appeals on online rumour dissemination are different. This thesis contributes to the existing literature in five aspects. First, it applies rumour theory to the context of social media and updates rumour theories by introducing expression certainty, use of evidence, source explicitness and source accessibility as new dimensions of information unambiguity. Second, this thesis investigates the effects of emotional pleasantness, activation and imagery on rumour dissemination, bringing new insights to rumour theories from emotion theories. Third, built on congruence theories and persuasion theories, this thesis investigates how topic-congruence and message-congruence moderates the effects of cognitive appeals and affective appeals on rumour dissemination. By doing so, this thesis extends rumour theory by combining the rumour context features and rumour message features. Moreover, this thesis identifies different types of online rumour topics and illustrates that online rumour messages are disseminated differently across rumour topics, enriching the understanding of online rumour dissemination on social media. Furthermore, while traditionally researchers have found it difficult to identify rumours and trace their disseminations, this thesis uses social media data to track rumours and their disseminations. Using social media data, this thesis tests the proposed research framework at rumour message level and explores the patterns of aggregate rumour message dissemination at rumour topic level. Practically, the findings of this thesis can be used to identify viral rumour messages so that practitioners can monitor and control rumours efficiently and effectively.